The Relationship of Body Length and Ratio Pappilla with Sex in Gobi Fish (Sicyopterus macrostetholepis) - Rona Taula Sari; Indra Junaidi Zakaria (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Research about the relationship of body length and ratio papilla with sex in goby fish (S. macrostetholepis Blkr.) has been done at Animal Structure and Developmental Laboratory, Biologi Department, Faculty of Matematics and Natural Sciences, Andalas University, Padang, which purposed to analyse the relationship of body length and ratio papilla with sex of goby fish (S. macrostetholepis Blkr.). The samples were taken in wild stream area at Batangkuranji river, Padang City. This research used descriptive method and data were analyzed by qualitatively and quantitatively. The results of investigation showed that in several goby fishes (S. macrostetholepis Blkr.) with different sex had the same of body length and the same of ratio papilla. So, there was not relationship between of body length and ratio papilla with sex. Goby fishes (S. macrostetholepis Blkr.) it belongs to the hermaphrodite protogini, which the androgynous young females, while in adulthood, it would change sex to male. The results of this study are expected to add to the treasures of knowledge and information about reproductive gobies (S. macrostetholepis Blkr.) in the preservation and development of fish farming.